MEKANISME PEMUNGUTAN PAJAK ATAS PEMINDAHAN HAK PADA JUAL BELI TANAH DAN BANGUNAN DI KABUPATEN KEPULAUAN SIAU TAGULANDANG BIARO (SITARO) - Pudihang, Sela; Morasa, Jenny; Gamaliel, Hendrik (Universitas Sam Ratulangi, 2017)
The BEA acquisition of Rights over the land and building tax is imposed on the acquisition of land rights and buildings. The tax was enacted by the Central Government into tax areas since January 2011. Islands Regency Siau In Indonesia this tax set forth in applicable local Islands Regency Siau In Indonesia number 5 in 2011 about tax areas. The purpose of the study to analyze the tax collection mechanism BPHTB Islands Regency Siau In Indonesia. Methods of analysis used qualitative descriptive. Data collection is done by the method of interview, observation and documentation. The research results of the tax collection mechanism BPHTB through stage charging SSPD BPHTB, stage counting BPHTB payable, the payment stage, verification has not been effective. To improve the understanding of the taxpayers of the County Financial Agency then BPHTB Siau In Indonesia more being proactive by increasing the activities of socialization, because of taxpayer compliance in reporting the Bea acquisition of Rights over the land and buildings in the Regency Siau In Indonesia is still lacking.Keywords: tax collection Mechanisms, BPHTB, buying and selling land and buildings